Response to Immune Checkpoint Inhibitor Treatment in Advanced Cervical Cancer and Biomarker Study - Shieh, Kevin R.; Huang, Anna; Xu, Yiqing (Frontiers in Medicine, 2021)
Background: Checkpoint inhibitor immunotherapy in refractory cervical cancer yielded an objective response rate (ORR) of 12% in tumors expressing the programmed cell death ligand-1 (PD-L1) in the KEYNOTE-158 phase II study. We hypothesized that the positive response might correlate with the level of PD-L1 expression and/or the tumor mutation burden (TMB). We also aimed to analyze if responses could be associated with platinum sensitivity. Methods: This is a retrospective study of all consecutive patients with cervical cancer who received pembrolizumab or nivolumab. Results: Ten patients were identified. Median age was 64.5 years old (range 48-80). The response rate was 70% and the median duration of response was 21.0 months after 20.7 months of follow-up (range 2.04-31.0). The response rate was 80% in patients with PD-L1 combined positive score (CPS) ≥ 10, and 75% in patients with TMB ≥ 10 mut/Mb. The mean progression-free survival (PFS) for the entire cohort was 16.5 months (95% CI 8.4-24.6), and the median PFS was 20.14. Nine patients had treatment for > 6 months. Five patients were platinum-sensitive and 5 were platinum-resistant at the time of immunotherapy, and the response rate was similar regardless of platinum sensitivity. Conclusions: The positive response to IO treatment in advanced cervical cancer in this study was higher than published, and a positive correlation with the level of PD-L1 expression and the TMB level was suggested. A PD-L1 CPS score ≥ 10 or TMB ≥ 10 may be biomarkers to correlate with response, which should be explored in large studies.